Moderating Role Of Institutional Ownership On The Effect Of Growth Opportunity, Free Cash Flow, Leverage, Liquidity And Profitability On Dividend Policy - Naufal Amara Syihan; Najmudin, Najmudin; Ekaningtyas Widiastuti; Hasibuan, Reza Rahmadi Hasibuan (International Journal of Technology and Education Research, 2024)
The purpose of this research is to analyze the effect of growth opportunity, free cash flow, leverage, liquidity, profitability, and institutional ownership toward dividend policy of property and real estate (PRE) companies listed on the IDX. The sample for this research is PRE companies listed on the IDX which have published complete annual reports for 2016-2021, there are 41 companies. The results of the study show that growth opportunity and leverage have no significant effect on the dividend payout ratio (DPR). meanwhile free cash flow, liquidity and profitability have a significant effect on the DPR of property and real estate companies. In addition, the results of the study show that institutional ownership does not moderate the effect of growth opportunity on the DPR. Whereas institutional ownership moderates the effect of free cash flow, leverage, liquidity, and profitability on DPR.